Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Motivasi Kerja, terhadap Loyalitas Pegawai di Kantor Camat Simpang Empat Kabupaten Asahan - Novita Sari; Abdul Rahman (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Employee loyalty is an important factor in supporting organizational performance and public service quality. Low levels of loyalty may reduce employee productivity, commitment, and responsibility in carrying out organizational duties. Therefore, organizations need to understand the factors that can improve employee loyalty. The purpose of this study was to analyze the partial and simultaneous effects of job satisfaction, work environment, and work motivation on employee loyalty. This research employed a quantitative approach with an associative research method. The population and sample consisted of 32 employees selected using a saturated sampling technique. Research data were collected through the distribution of Likert-scale questionnaires. The collected data were processed using SPSS version 25 and analyzed through multiple linear regression analysis. The results of the study indicated that job satisfaction, work environment, and work motivation had a positive and significant effect on employee loyalty, both partially and simultaneously. These findings demonstrate that improving employee satisfaction, creating a conducive work environment, and strengthening work motivation can enhance employee loyalty within the organization.